2021
DOI: 10.3390/ijerph18115813
|View full text |Cite
|
Sign up to set email alerts
|

Malaysian Health Literacy: Scorecard Performance from a National Survey

Abstract: Health literacy is an indicator of a society’s ability to make better health judgements for themselves and the people around them. This study investigated the prevalence of health literacy among Malaysian adults and provided an overall picture of the society’s current health literacy status, which has not been previously assessed. The study also highlighted socio-demographic markers of communities with limited health literacy that may warrant future intervention. A population-based self-administered survey usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…With respect to stereotyping, we found that females tended to do this more ( p = 0.005). In a study on Malaysians, Jaafar et al reported that females have better sufficiency in health literacy than their male counterparts ( 64 ), a result that was consistent with the finding from other countries ( 65 68 ). We did not, however, observe this in the present study.…”
Section: Discussionsupporting
confidence: 57%
“…With respect to stereotyping, we found that females tended to do this more ( p = 0.005). In a study on Malaysians, Jaafar et al reported that females have better sufficiency in health literacy than their male counterparts ( 64 ), a result that was consistent with the finding from other countries ( 65 68 ). We did not, however, observe this in the present study.…”
Section: Discussionsupporting
confidence: 57%
“…Health literacy was noted to be significantly associated with age, health status, and health problems [ 41 ]; it is also seen as an indicator by which to describe a nation’s health status. A national health literacy survey, including nearly 9500 individuals aged 18 and above, showed that limited health literacy groups were prevalent among respondents of an older age, a lower education level, and with a lower household income [ 42 ]. Another nationwide cross-sectional survey enrolling over 9000 Danish individuals aged ≥ 25 years showed that inadequate health literacy is strongly associated with a low socio-economic status, a poor health status, inactivity, and being overweight [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using the self-administered HLS-M-Q18 questionnaire, data were gathered. This questionnaire was developed and condensed from European Questionnaire 47 of the Health Literacy Survey (HLS-EU-Q47) (Jaafar et al, 2021;Mohamad et al, 2020). The European Health Literacy Survey Questionnaire (HLS-EU-Q47) is gaining popularity as a health literacy (HL) measurement instrument, notably in Malaysia.…”
Section: Methodsmentioning
confidence: 99%
“…The European Health Literacy Survey Questionnaire (HLS-EU-Q47) is gaining popularity as a health literacy (HL) measurement instrument, notably in Malaysia. (Jaafar et al, 2021) used confirmatory component analysis to compress the 47-item scale to a short scale with appropriate psychometric qualities for HL screening.…”
Section: Methodsmentioning
confidence: 99%